Production Guidelines for Globe Artichoke in Florida - Shinsuke Agehara (EDIS)
Globe artichoke (Cynara cardunculus L.) belongs to a genus of thistle-like plants in the sunflower (Asteracae) family and is cultivated for its flower buds. This 4-page fact sheet discusses production guidelines for artichoke in Florida. Written by Shinsuke Agehara and published by the Horticultural Sciences Department, February 2017.